Using Empirical Article Analyses to Assess Students Learning of Psychology Research Methods - Schiel, Michael; Graham, Kaetlyn; Richardson, Sarah (My University, 2012)
Bachiochi et al. (2011) developed an article analysis activity to assess psychology students' mastery of American Psychological Association student learning outcomes (SLOs) for research methods (Goal 2; APA 2007). Students read a research report and answered factual and analysis questions about it. Bachiochi et al. used the activity to assess their department's success at teaching research methods over a two-course sequence, finding that it both documented students' learning and identified ways in which they could improve their program. This study applied the Baciochi et al. approach to assess student attainment of the UWEC Psychology Department's SLOs for research methods.
Color poster with text and graphs.
Keywords: Cognition--Testing; College students--Wisconsin--Eau Claire--Psychology; Educational evaluation; Education, Higher--Evaluation; Psychology--Research--Evaluation; Posters